STRUKTUR PENYAJIAN KESENIAN REJUNG RINGIT DI DESA TANJUNG BULAN KECAMATAN PULAU BERINGIN KABUPATEN OKU SELATAN PROVINSI SUMATERA SELATAN - Hidayatullah, Fadhilah (Besaung : Jurnal Seni Desain dan Budaya, 2022)
Rejung is one of the local cultures of South Sumatra Province. The form of this art is a rhyme that uses the ethnic language "Semende". One of the speech literature that is rapidly developing in music is the art of rejung. Therefore, it is necessary to write down and know the parts of the dish in its original form. This article is the result of research that discusses the art of rejung as one of the local cultures that needs to be archived in the library. Therefore, the purpose of this study is to describe the structure of the presentation of the art of rejung ringit, which is in Tanjung Bulan village, Pulau Beringin sub-district, South OKU district. The research method used is a qualitative descriptive approach. While the technique of collecting data by means of observation, documentation, and interviews. The results showed that in the art of rejung ringit there are three parts, namely; Beginning, Essence, and Closing. The initial part is the term "inviting" by playing only musical instruments. The core part is done by combining musical instruments with vocals. The closing section presents musical instruments without back vocals. The musical instruments used are itar (guitar), gambus, and piul (violin). The three musical instruments function as musical accompaniments to the art of rejung which is performed "Setebah". While the vocals stand alone as well as the main melody in the art of rejung.